Rezension zu: „Vielleicht...Ein hebräisches Modalwörtchen und seine Bedeutung für eine Theologie der Hoffnung” - Bergmann, Claudia Dorit (Theologische Literaturzeitung)

'Look to Abraham and Sarah' - Bergmann, Claudia Dorit; Latt, May May (Imitating Abraham: Ritual and Exemplarity in Jewish and Christian Contexts)

Circular product design: a literature-based identification of challenges from the perspective of product designers - Jagnow, Jan; Stöhr, Bernd; Bernijazov, Ruslan; Koldewey, Christian; Dumitrescu, Roman (Proceedings of the Design Society)
ABSTRACT: The importance of the circular economy as an alternative to today’s prevailing linear economy is recognised in both industry and research. Product designers are having a major influence on this transition by adapting the characteristics of physical products in the early phases of the product development process. However, most products follow a linear approach and are far from being circular. This paper aims to identify the challenges that product designers face when designing circular products. Building on a developed understanding of related terms in circular product design, an exploratory literature review is conducted. The results help to gain an overview and understanding of the challenges that need to be addressed. Therefore, further research directions are derived to support the transition from linear to circular products in the long term.

Effective management support for design: towards a model of managerial competence - Stöhr, Bernd; Koldewey, Christian; Bernijazov, Ruslan; Dumitrescu, Roman (Proceedings of the Design Society)
ABSTRACT: Well-designed products are crucial to a company's business success. Management support is a critical success factor in ensuring that design-related aspects are given appropriate attention during product development. Despite the importance of management, the literature doesn't provide a clear picture of what characterizes a competent manager in product design. This gap impedes competence development and explains why organizations struggle to leverage the benefits of well-designed products. This research aims to address this gap by synthesizing important findings from the literature into a model of managerial competence. The model provides initial insight into the individual competencies managers need to meet their responsibility for good product design in organizations.

„Ins Offene“. Die räumliche Verlagerung jüdischer Mahlrituale in antiken jüdischen Texten und modernen Krisenzeiten. - Bergmann, Claudia Dorit (Grenzgänge: Beiträge für eine Liturgiewissenschaft zwischen akademischem Diskurs, pluraler Kultur und kirchlichem Leben. Festschrift für Benedikt Kranemann.)

Crime Fever. Colonial Pathologies in Émile Zola’s Thérèse Raquin (1867) - Schlieper, Hendrik (Bodies, Remedies, Policies. From Early Modern Chronicles of the Indies to Covid-19 Narratives)

Labern als Beruf? Schriftsteller-Intellektuelle im Podcast - Heise, Tillmann (Literatur und Podcast. Inszenierungsformen – Rezeptionsmodelle – Wissenskommunikation)

HD Mapping as enabler for autonomous systems on airports - Seidenberg, Tobias; Stöhr, Bernd; Eckertz, Daniel; Jagnow, Jan; Dumitrescu, Roman (Proceedings of the 2024 9th International Conference on Information Systems Engineering)

Zwischen Konkurrenz und Kooperation - Staffel, Florian

Cooperation and Catching up - Staffel, Florian (Security Strategies in International Business History)

Neue Perspektiven der Unternehmensgeschichte [New Perspectives in Business History]: Edited by Nina Kleinöder, Christian Marx, Boris Gehlen, Juliane Czierpka, Brill/Schöningh, Paderborn, 2024 - Staffel, Florian (Business History)

Datenraum Kultur - Neue Forschung aus dem Projekt - Althaus, Maike

Startschuss für die digitale Zukunft - Das Digital Talents Program geht in die nächste Runde - Kundisch, Dennis

Zahlenmuster und Brüche: Eine Lernumgebung zum algebraischen Denken - Rezat, Sebastian; Doligkeit, Nadja (mathematik lehren)

In vacuum metasurface for optical microtrap array - Li, Donghao; Liao, Qiming; Xu, Beining; Zentgraf, Thomas; Narvaez Castaneda, Emmanuel; Zhou, Yaoting; Qin, Keyu; Xu, Zhongxiao; Shen, Heng; Huang, Lingling (Optics Express)
Optical tweezer arrays of laser-cooled and individually controlled particles have revolutionized atomic, molecular, and optical physics. They afford exquisite capabilities for applications in quantum simulation of many-body physics, quantum computation, and sensing. Underlying this development is the technical maturity of generating scalable optical beams, enabled by active components and a high numerical aperture objective. However, such a complex combination of bulk optics outside the vacuum chamber is very sensitive to any vibration and drift. Here, we demonstrate the generation of a 3 × 3 static tweezer array with a single chip-scale multifunctional metasurface element in vacuum, replacing the meter-long free space optics. Fluorescence counts on the camera validate the successful trapping of the atomic ensemble array and showcase a promising strategy for integrated photonics with cold atom systems. The introduction of a polarization independent dual-wavelength metasurface significantly enhances fluorescence collection efficiency while reducing experimental complexity. This approach paves the way for scalable neutral atom platforms and offers a compelling route towards the realization of next generation quantum metasurfaces.

Christoph Haar (Hg.): Slavery, Law and Religion in the Early Modern Period (Law and Religion in the Early Modern Period/ Recht und Religion in der Frühen Neuzeit. 7). Leiden, Boston 2024 - Priesching, Nicole (Theologische Revue)

Berichtete Praktiken der Lernbegleitung bei der Förderung von arithmetischen Basiskompetenzen - Neufeld, Inga (Was ist wichtig? Perspektiven auf den Mathematikunterricht der Grundschule)

Antonio Negri, Spinoza, Marx, and Digital Capitalism. - Fuchs, Christian (Philosophy and Social Criticism)

Technikrecht - Ensthaler, Jürgen; Gesmann-Nuissl, Dagmar; Müller, Stefan

A Measurement Setup for the Determination of Temperature-Dependent Viscoelastic Material Parameters Using an Ultrasonic Pulse-Echo Technique - Dreiling, Dmitrij; Itner, Dominik; Gravenkamp, Hauke; Birk, Carolin; Henning, Bernd (2025 International Congress on Ultrasonics)